Pengaruh Kepuasan Kerja dan Peran Mediasi Locus of Control terhadap Kinerja Pegawai di Badan Kepegawaian Daerah Provinsi Maluku - Magdalena Natasia Sapulette; Petronela Sahetapy; Stanislaus Kostka Ohoiwutun (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the influence of job satisfaction and the mediating role of locus of control on employee performance at the Regional Civil Service Agency of Maluku Province. Using a descriptive–quantitative design with causal-correlational orientation, the study involved a population of 144 employees, with 100 respondents selected through simple random sampling. Data were analyzed using path analysis. The results indicate that locus of control significantly enhances job satisfaction and employee performance, while job satisfaction also significantly improves performance. Moreover, locus of control indirectly affects performance through its positive impact on job satisfaction. These findings suggest that fostering an internal locus of control and improving job satisfaction can serve as practical strategies to enhance employee performance and inform theoretical models of organizational behavior.